Competence of expertise, experience, auditor professional skeptism and audit situation to the relevance of providing audit opinion on entity's financial statements - Padlah Riyadi, Padlah Riyadi (Cebong Journal, 2023)
This research is to examine and provide empirical evidence that the factor of expertise, experience, professional skepticism of auditors and audit situations has no effect or no relevance to the provision of audit opinion on the financial statements of the entity. This research was conducted using the sampling method, namely purposive sampling, with the type of quantitative research. The data was analyzed using multiple regression analysis models. Hypothesis testing is done to determine the extent of expertise, experience, professional skepticism of auditors and audit situations affect the relevance of the provision of audit opinion on the financial statements of entities either partially or simultaneously.